Land cover and socio-economic dynamics of coffee to oil palm land conversion in Way Kanan, Indonesia - Hernanda, Tiara Aprilia Putri; Fauzi, Akhmad; Barus, Baba; Arifin, Bustanul (Brawijaya University, 2026)
The expansion of oil palm in Indonesia increasingly occurs at the expense of traditional perennial crops such as coffee, reshaping land systems and livelihoods. This study analyzed coffee to oil palm conversion in Way Kanan Regency, Lampung Province, from 2018 to 2024 through GIS-based classification, satellite imagery, and field validation. Results revealed a sharp decline in forest cover of around 63% during those periods and the dominance of agricultural lands (197,000 ha), driven primarily by oil palm expansion. Results showed that in Kasui, coffee agroforestry followed a boom and bust trajectory with a 59% increase, but was later displaced by oil palm, which surged by 52%. Results indicated that in Rebang Tangkas, coffee maintained a modest presence with a 36% increase, while oil palm expanded aggressively by 329%, underscoring its dominant role in reshaping land use dynamics. Conversion patterns were amplified by topography and accessibility, with oil palm concentrated in lowlands and coffee surviving in uplands. Institutional frameworks and economic incentives reinforced oil palm dominance, while rising coffee prices have triggered localized reconversion. These findings highlight a dual transition: oil palm consolidation in accessible lowlands and the persistence of coffee agroforestry in upland niches. The study underscores the urgency of place-based governance to reconcile economic drivers with ecological sustainability and rural livelihood resilience.